TEMPE, BANANA BUD AND MORINGA NUGGET (TEJAKE NUGGET) AS ALTERNATIVE HEALTH AND NUTRITIOUS SNACK - Nangsih Sulastri Slamet (International Interdisciplinary Conference on Sustainable Development Goals, 2019)
Nugget is a food product which can be used as an alternative snack. One way to get the benefits of tempe, banana bud and moringa is by making processed nuggets which are healthy and nutritious snacks. The purpose of this study was to determine the level of preference and nutritional value of the Tejake nugget. The research method is a quantitative test with an experimental approach and uses 25 panelists to see the level of preference based on organoleptic tests. Data were analyzed using the Friedman and Wilcoxon tests. Nutritional value is determined using the Nutrisurvey application. Organoleptic test results based on the highest level of preference on the taste and texture of the Tejake nugget were in the T2 treatment and the highest level of preference on color and flavor were in the T1 treatment. Based on the Friedman and Wilcoxon test, from the organoleptic test performed, the three parameters namely color, flavor and texture have a significant value smaller than 0.05 (p <0.05), whereas for the taste parameter the significant value is greater than 0 .05 (p> 0.05). This shows that the substitution of banana bud and moringa leaves does not affect the taste of Tejake nuggets produced. The high nutritional value of Tejake nuggets can makes an alternative to healthy and nutritious snacks